Psychometric evaluation of the PROMIS® Depression Item Bank: an illustration of classical test theory methods - Sandra Nolte; Cheryl Coon; Stacie Hudgens; Mathilde G. E. Verdam (Journal of Patient-Reported Outcomes, 2019)
Abstract Background Psychometric theory offers a range of tests that can be used as supportive evidence of both validity and reliability of instruments aimed at measuring patient-reported outcomes (PRO). The aim of this paper is to illustrate psychometric tests within the Classical Test Theory (CTT) framework, comprising indices that are frequently applied to assess item- and scale-level psychometric properties of PRO instruments. Methods Using data on the PROMIS Depression Item Bank, typical CTT indices for the assessment of psychometric properties are illustrated, including content validity, item-level data exploration, reliability, and construct validity, particularly confirmatory factor analysis, to test the unidimensionality assumption underlying the item bank. Analyses are carried out on an original item set of 51 depression items, the final (official) PROMIS Depression Item Bank consisting of 28 items, and an 8-item short form. Results The analyses reported provide an informative illustration on how item- and scale-level reliability and validity statistics can be used to assess the psychometric quality of a PRO instrument. The results illustrate how the reported statistics can be used for item selection from an item pool (here: 51 items). Both the (final) 28-item bank and the 8-item short form show good psychometric properties supporting the high quality of individual items and the unidimensionality assumption of the item bank. Conclusions It is our hope that our illustration of CTT methods, in conjunction with two companion papers illustrating modern test theory methods, will help researchers to confidently apply a range of statistical tests to evaluate item- and scale-level psychometric performance of PRO instruments.